Usefulness of Electronic Medical Records Technology for Nurse Managers: A Literature Review - Inggerid Agnes Manoppo; Rr Tutik Sri Hariyati (Universitas STRADA Indonesia, 2021)
Nurse managers play an important role in evaluating medical records through management activities, namely planning, organizing, actuating and controlling (POAC) that are carried out conventionally. Nurse managers play an important role in evaluating medical records through management activities, namely planning, organizing, actuating and controlling (POAC) that are carried out conventionally. Now medical records have evolved into integrative Electronic Medical Records (EMR). This review aims to explore the usefulness of EMS technology for nurse managers. Literature searches use two database sources namely ProQuest and Google Scholar with boolan search